Highly efficient tandem organic light-emitting devices employing an easily fabricated charge generation unit. (11th January 2018) - Yang, Huishan; Yu, Yaoyao; Wu, Lishuang; Qu, Biao; Lin, Wenyan; Yu, Ye; Wu, Zhijun; Xie, Wenfa
Abstract: We have realized highly efficient tandem organic light-emitting devices (OLEDs) employing an easily fabricated charge generation unit (CGU) combining 1, 4, 5, 8, 9, 11-hexaazatriphenylene-hexacarbonitrile with ultrathin bilayers of CsN3 and Al. The charge generation and separation processes of the CGU have been demonstrated by studying the differences in the current density–voltage characteristics of external-carrier-excluding devices. At high luminances of 1000 and 10000 cd/m 2, the current efficiencies of the phosphorescent tandem device are about 2.2- and 2.3-fold those of the corresponding single-unit device, respectively. Simultaneously, an efficient tandem white OLED exhibiting high color stability and warm white emission has also been fabricated.